Pengaruh Komitmen Organisasi, Gaya Kepemipmpinan dan Lingkungan Kerja Terhadap Kinerja Karyawan RSUD Waras Wiris Kabupaten Boyolali - Moza Putri Pujayanti; Sudarmadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The study's goal was to ascertain how the work environment, leadership style a1nd orga1nizational comfmitment affected thfe perforfmance of the staff aft Waras Wiris Hopspital in Boyolali Regency. The population of Waras Wiris Hospital employees in Boyolali Regency served as the research sample. Forty responders made up the study's sample. Saturated samples and questionnaires were employed in the sampling process. Multirple linefar regrgession analysis was the analysis method employed. The findings demonstrated thtat the wrork envirofnment, leardersghip stysle, and organizational commitment all significantly impacted the performance of the staff at Waras Wiris Hospital in Boyolali Regency.